Fundamental issuesIn the book Al-Bustan in the parsing of the problems of the Qur’an by Ibn Al-Ahnaf Al-Yemeni (d. 717 AH) - Hamdi, Saja Adnan; Alawi, Taher Saleh (Journal of Ecohumanism, 2024)
Al-Bustan fi I'rab Mushkil al-Qur'an by Ibn Al-Ahnaf Al-Yemeni (d. 717 AH) is a seminal work in Qur'anic linguistics, offering an in-depth analysis of the grammatical and syntactical complexities of the Qur'an. The author meticulously addresses ambiguous structures, polysemous words, and variations in canonical readings (qira’at), providing linguistic and theological insights that harmonize with the Qur'an's eloquence and unity. By employing the principles of Arabic grammar (nahw), morphology (sarf), and contextual analysis, Ibn Al-Ahnaf resolves apparent contradictions and clarifies rhetorical features, showcasing the linguistic sophistication of the Qur'an. The book bridges the gap between language and theology, demonstrating how grammatical parsing (i'rab) enhances the understanding of Qur'anic meanings while safeguarding doctrinal integrity. Designed as a resource for scholars and students alike, Al-Bustan remains a pivotal reference in Qur'anic exegesis and Arabic grammar, reflecting its enduring significance in Islamic scholarship.